Kualitas Sentral Pelayanan Kepolisian Terpadu (SKPT) dalam Meningkatkan Kepuasan Masyarakat di Wilayah Kepolisian Resor (POLRES) Kabupaten Biak Numfor - Kiki Reskia; Rahmah Agustiani; Luluk Endang Nurrokhmah (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
This study aims to analyze the quality of services at the Integrated Police Service Center (SPKT) of the Biak Numfor Police Department in improving public satisfaction. This research employs a qualitative narrative method with samples including the Head of SPKT of the Biak Numfor Police, police officers assigned to the SPKT, and community members who received SPKT services. The data collection instrument used was interviews. The findings indicate that the services provided by the Biak Numfor Police officers, particularly in terms of attitude, communication, and fairness, have been satisfactory. The friendly demeanor of the officers, such as smiling while receiving reports or complaints, leaves a positive impression on the community. However, certain aspects of the service remain below public expectations, including timeliness in following up on reports, clarity in case resolution, and officer discipline in service delivery. Additionally, there were some practices perceived by the community as lacking consistency, which affected the overall service quality. According to public surveys, these issues result in less-than-optimal satisfaction with the services at SPKT Biak Numfor Police.